1. The problem statement, all variables and given/known data If z= x2 - y2 + xy x = w + 4t y = w2 -5t + 4 w = r2 - 5u t = 3r + 5u find ∂z/∂r 2. Relevant equations 3. The attempt at a solution This is going to be quite long and tedious so bare with me, but here is my work. drawing a diagram to help out a bit. ∂z/∂r = (∂z/∂x)(∂x/∂w)(∂w/∂r) + (∂z/∂x)(∂x/∂t)(∂t/∂r) + (∂z/∂y)(∂y/∂w)(∂w/∂r) + (∂z/∂y)(∂y/∂t)(∂t/∂r) =(2x-y)(1)(2r) + (2x-y)(4)(3) + (-2y+x)(2w)(2r) + (-2y + x)(-5)(3) now is that the final answer? or should everything be in terms of r?